2011
DOI: 10.1002/hep.24218
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of clathrin heavy chain staining in a marker panel for the diagnosis of small hepatocellular carcinoma

Abstract: The American Association for the Study of Liver Diseases guidelines recommend the use of all available markers for improving the accuracy of the diagnosis of small hepatocellular carcinoma (HCC). To determine whether clathrin heavy chain (CHC), a novel HCC marker, is effective in combination with glypican 3 (GPC3), heat shock protein 70, and glutamine synthetase, we compared the performances of a three-marker panel (without CHC) and a four-marker panel (with CHC) in a series of small HCCs ( 2 cm) and nonsmall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 78 publications
(110 reference statements)
0
44
1
Order By: Relevance
“…During carcinogenesis, a change in the vascular support is a hallmark of the evolution to pHCC, which can be demonstrated by the use of endothelial markers [10] [11]. Difficult cases however are in need of a more dedicated approach, contemplating the use of a robust panel of biomarkers as that already validated (GPC3-Glypican 3, HSP70-Heat shock protein 70, GS-Glutamine synthetase) [12] [13] [14], which has absolute specificity but limited sensitivity and of markers recently suggested as diagnostically useful, such as CHC (clathrin heavy chain) [15] and EZH2 (Enhancer of zeste homologue 2) [16].…”
Section: Introductionmentioning
confidence: 99%
“…During carcinogenesis, a change in the vascular support is a hallmark of the evolution to pHCC, which can be demonstrated by the use of endothelial markers [10] [11]. Difficult cases however are in need of a more dedicated approach, contemplating the use of a robust panel of biomarkers as that already validated (GPC3-Glypican 3, HSP70-Heat shock protein 70, GS-Glutamine synthetase) [12] [13] [14], which has absolute specificity but limited sensitivity and of markers recently suggested as diagnostically useful, such as CHC (clathrin heavy chain) [15] and EZH2 (Enhancer of zeste homologue 2) [16].…”
Section: Introductionmentioning
confidence: 99%
“…22 Similarly, Cai et al suggested the use of the enhancer of EZH2 (zeste homologue 2) in combination with GPC-3 and HSP-70. 23 Arginase-1, an enzyme of the urea cycle, has been shown to be more sensitive than HepPar-1 in detecting poorly differentiated HCCs.…”
Section: Glutamine Synthetase (Gs) Is Expressed In the Normal Liver Inmentioning
confidence: 98%
“…With the 4-maker panel, staining by at least 2 markers shows a diagnostic accuracy of 97% and 84.3% in non-small HCCs and small HCCs, respectively. CHC was also reported as the most single sensitive marker for small grade 1 HCC, giving a sensitivity of 58.8%, versus GS (41.2%), HSP70 (17.6%) and GPC3 (11.8%) [46] (Figure 2). Future perspectives on this topic will be the use of GPC-3 as a prognostic marker for HCC.…”
Section: Three-marker Panel (Hsp70 Gpc-3 and Gs)mentioning
confidence: 99%
“…[46] . With the 4-maker panel, staining by at least 2 markers shows a diagnostic accuracy of 97% and 84.3% in non-small HCCs and small HCCs, respectively.…”
Section: Three-marker Panel (Hsp70 Gpc-3 and Gs)mentioning
confidence: 99%